2021
DOI: 10.1017/s1368980021003967
|View full text |Cite|
|
Sign up to set email alerts
|

Ultra-processed food consumption, socio-demographics and diet quality in Australian adults

Abstract: Objective: To examine how socio-demographic characteristics and diet quality vary with consumption of ultra-processed foods (UPFs) in a cross-sectional nationally representative survey of Australian adults. Design: Using a 24-hour recall, this cross-sectional analysis of dietary and socio-demographic data classified food items using the NOVA system, estimated the percentage of total energy contributed by UPFs and assessed diet quality using the Dietary Guideline Index (DGI – 2013 total a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
43
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 59 publications
(93 reference statements)
10
43
4
1
Order By: Relevance
“…The lack of nutritional education, together with marketing strategies and the reduced prices of UPFs, easily mislead consumers, promoting its consumption. These findings are consistent with previous results about the inverse association between educational level and UPF consumption [ 7 , 9 , 10 ]. Nevertheless, studies conducted in Brazil, Colombia, and Mexico reported a higher UPF intake among the richest individuals with higher educational levels [ 13 , 15 , 16 ].…”
supporting
confidence: 93%
See 3 more Smart Citations
“…The lack of nutritional education, together with marketing strategies and the reduced prices of UPFs, easily mislead consumers, promoting its consumption. These findings are consistent with previous results about the inverse association between educational level and UPF consumption [ 7 , 9 , 10 ]. Nevertheless, studies conducted in Brazil, Colombia, and Mexico reported a higher UPF intake among the richest individuals with higher educational levels [ 13 , 15 , 16 ].…”
supporting
confidence: 93%
“…In addition, a worse dietary profile (higher energy density, and higher intake of total carbohydrates, free sugar, and total and saturated fat) was associated with UPF consumption, young individuals showing the highest UPFs consumption. Similar results have been reported by Marchese et al [ 9 ] and Magalhães et al [ 7 ], who showed how sociodemographic characteristics (age, gender, educational level, marital status, smoking status, living in disadvantaged areas or with lower socioeconomic position) and diet quality modify the consumption of UPF. There is strong evidence for the association between age and UPF consumption.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The availability of biomarker data in the NHS was limited to 3,299 individuals from a sample of more than 20,000, which could have introduced potential for selection bias. Finally, a recent Australian study analysing consumption of ultra-processed foods reported that the second lowest household income quintile had the higher rates of ultra-processed food consumption in Australia, which could have an impact on CVD risk [43].…”
Section: Discussionmentioning
confidence: 99%